2012
DOI: 10.1155/2012/941082
|View full text |Cite
|
Sign up to set email alerts
|

Development of Screening Tools for the Interpretation of Chemical Biomonitoring Data

Abstract: Evaluation of a larger number of chemicals in commerce from the perspective of potential human health risk has become a focus of attention in North America and Europe. Screening-level chemical risk assessment evaluations consider both exposure and hazard. Exposures are increasingly being evaluated through biomonitoring studies in humans. Interpreting human biomonitoring results requires comparison to toxicity guidance values. However, conventional chemical-specific risk assessments result in identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It has also been used as a first-level screening tool to prioritize for review a large number of substances identified as needing an assessment under the Canadian Environmental Protection Act (Health Canada, 2016). Consideration has also been given to whether the TTC approach could be applied to human biomonitoring data (Becker et al, 2012) and to human exposures by non-oral routes (Carthew et al, 2009;Escher et al, 2010;Hennes, 2012;Kroes et al, 2007;Partosch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used as a first-level screening tool to prioritize for review a large number of substances identified as needing an assessment under the Canadian Environmental Protection Act (Health Canada, 2016). Consideration has also been given to whether the TTC approach could be applied to human biomonitoring data (Becker et al, 2012) and to human exposures by non-oral routes (Carthew et al, 2009;Escher et al, 2010;Hennes, 2012;Kroes et al, 2007;Partosch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For many chemicals health-based guidance values developed by government agencies using transparent, peer-reviewed methods are unavailable. In such cases, if sufficient animal toxicity data are available, provisional (screening level) guidance values can be derived using the POD values from the key study, after applying adjustment factors (Sand et al, 2011;Becker et al, 2012). Based on the robustness of the toxicity data (e.g., whether the critical data are based on chronic versus acute animal studies), additional UF may need to be considered.…”
Section: Health-based Exposure Guidance Valuesmentioning
confidence: 99%
“…Based on the robustness of the toxicity data (e.g., whether the critical data are based on chronic versus acute animal studies), additional UF may need to be considered. For several high production volume chemicals, the lowest observable adverse effect level (LOAEL) and NOAEL values could be used as the starting point to derive screening level health-based exposure guidance values (Becker et al, 2012). Chemicals that lack robust toxicity data pose a major challenge for deriving health-based guidance values.…”
Section: Health-based Exposure Guidance Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous biomonitoring studies have measured concentrations of these chemicals in biological specimens like blood, urine, adipose tissue, and breast milk. To assess the biological relevance of these findings, different approaches have been extensively discussed by Hays et al (2008) and Becker et al (2012). Normally, for a biomonitoring-based risk assessment, the actual exposures to chemicals are compared with the exposure at the relevant PoD which, for the purpose of interpretation of biomonitoring results, can be defined as an internal exposure-response point that marks the threshold above which the incidence begins to increase, thus allowing biomonitoring data to be placed within a public health risk context (Hays et al, 2008).…”
Section: Hazard Quotients (Hqs)mentioning
confidence: 99%